Evidence for the Psychometric Properties of Component Test Items in the Eurofit Test Battery administered to Elite Schoolboy Rugby Union Players: A Test-retest Reliability Study - Tafadzwa Mupondi; Tonderai Washington Shumba; Christiane Von Der Heiden; Farirai Kamba; Matthew Chiwaridzo (Central European Journal of Sport Sciences and Medicine, 2024)
Rugby is a popular sport and requires participants to have commensurate physical attributes for effective participation. One physical fitness test battery which enjoys extensive use contextually is the European Test of Physical Fitness (Eurofit). However, the psychometric properties of the test battery have not been explored and documented in the local context. Therefore, this study was conducted to examine the test-retest reliability of the Eurofit test battery items among elite schoolboy rugby players in Harare, Zimbabwe. Thirty-two (32) players with the mean age of 17.2 (SD=1.03) years completed all the tests during the in- season period. Anthropometric and Eurofit test measurements were obtained twice with seven days separating the assessments. The Intraclass Correlation Coefficient (ICC) estimated the reliability test items. The global ICCs for the Eurofit test items ranged from 0.59 to 0.98. The Sit-and-Reach test yielded the highest temporal reliability (ICC=0.98). The Plate Tapping test, Flamingo Balance test and 10×5m Shuttle Run test showed ICCs < 0.7. Cognisant of the study limitations, some component test items of Eurofit test battery can be recommended for reliably evaluating aspects of physical fitness in junior rugby players in Zimbabwe whilst others still need consideration and test modification.